Survival rate of osseointegrated implants in atrophic maxillae grafted with calvarial bone: a retrospective study - Quiles, J. C.; Souza, F. A. [UNESP]; Bassi, A. P. F. [UNESP]; Garcia, I. R. [UNESP]; Franca, M. T.; Carvalho, P. S. P. [UNESP] (Churchill Livingstone, 2015)
The aim of this study was to evaluate the clinical survival rate of osseointegrated implants placed in the atrophic maxilla that has been reconstructed by means of autogenous bone grafts harvested from a cranial calvarial site. Further, we sought to analyse the level of pen-implant bone after prosthetic rehabilitation and to determine subjective patient satisfaction with the treatment performed. This study conformed to the STROBE guidelines regarding retrospective studies. Twenty-five patients who had received osseointegrated implants with late loading in the reconstructed atrophic maxilla were included in the study. The survival rate and level of pen-implant bone loss were evaluated. A questionnaire related to the surgical and prosthetic procedures was completed. The observed implant survival rate was 92.35%. The mean bone loss recorded was 1.76 mm in the maxilla and 1.54 mm in the mandible. The results of the questionnaire indicated a high level of patient satisfaction, little surgical discomfort, and that the patients would recommend the procedure and would undergo the treatment again. From the results obtained, it is concluded that the cranial calvarial site is an excellent donor area; calvarial grafts provided stability and maintenance of bone volume over the course of up to 11 years.
Keywords: bone graft; cranial calvarial; osseointegrated implants; implant survival; marginal bone loss; subjective evaluation